PERBEDAAN HASIL BELAJAR PERBANKAN SISWA MENGGUNAKAN MODEL PEMBELAJARAN WORD SQUARE DAN MODEL PEMBELAJARAN TALKING STICK KELAS X SMA SWASTA YPK MEDAN TA 2021-2022 - Hajjah Analisa Purba; Samio Samio (Jurnal Inovasi Penelitian, 2022)
Study aims to find out whether there is a significant difference between student banking learning outcomes using the Word Square learning model and the Talking Stick learning model in class X Social Sciences SMA Swasta YPK Medan. This type of research is an experimental study with the entire population of class X Social Sciences SMA Private YPK Medan FY 2021-2022 which consists of 2 classes totaling 62 people. The samples taken in this study were 2 classes totaling 32 students and 30 students, namely class X IPS 1 as an experimental class using the Word Square learning model and class X IPS 2 as a control class using the Talking Stick learning model. as many as 62 people. The instrument used to measure students' banking learning outcomes was in the form of 30 multiple choice questions. The technique used is hypothesis testing using t-test. The results showed that the average value of student learning outcomes using the Word Square learning model was 87.18 which was classified as good. while the average score of students who use the Talking Stick model is 80.93 which is quite good. From the results of hypothesis testing with a significant level of = 0.05, the price = 3.004, while from the student's t distribution table, the price = 1.67. Because it means it is accepted, it can be concluded that there are differences in learning outcomes in Banking which are taught with the Word Square learning model and those taught with the Talking Stick learning model in class X Social Studies at YPK Private High School Medan FY 2021-2022.